PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP KINERJA KARYAWAN - Putra, Kadek Mahendra; Adnyani, IGA Dewi (E-Jurnal Manajemen; Vol 5 No 7 (2016), 2016)
This study aimed at analyzing the effect of transformational and OCB leadership on employee performance with organizational commitment mediation. This research was conducted at PT. BPR Jaya Kerti. Sampling of this study made use census method with 46 employees. The data were collected through interviews and questionnaires. Data analysis techniques applied in this research was the analysis of the path. The results of the study showed that; 1) transformational leadership had positive and significant effect on organizational commitment, 2) the transformational leadership showed positive and significant effect on employee performance, 3) the OCB indicated positive and significant effect on organizational commitment, 4) the OCB had positive and significant effect on employee performance, 5) organizational commitment and significant showed positive effect on employee performance.
Keywords: Transformational leadership, OCB, Organizational Commitment, Employee Performance.